Safety of Intravenous Valproate - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
A multicenter. open-label study of the safety of intravenous sodium valproate in 318 hospitalized patients with epilepsy is reported from the NYU Hospital for Joint Diseases; MINCEP Epilepsy Care and Minnesota Epilepsy Group, MN; University of Texas, Houston; Medical College of Virginia, Richmond; Bowman-Gray School of Medicine, Winston-Salem, NC; and University of Miami, FL.